PF.04 Abnormal Platelet Reactivity in Pregnancies Complicated by Intrauterine Growth Restriction. (26th April 2013) - Mullers, S; Burke, N; Flood, K; O'Connor, H; Dempsey, M; Cotter, B; Tully, E; Dicker, P; Geary, M; Kenny, D; Malone, FD
Abstract : Platelet function in pregnancies complicated by intra-uterine growth restriction (IUGR) is not well understood. We sought to evaluate platelet function in response to multiple concentrations of multiple agonists in pregnancies complicated by IUGR using a novel platelet function assay. Cases of intrauterine growth restricted singleton pregnancies were recruited following ultrasound diagnosis between 24–40 weeks gestation (estimated fetal weight <10 th centile for gestational age) in a tertiary referral centre. A modification of standard light transmission aggregometry was used to assess platelet reactivity. Several agonists were assessed at incremental concentrations to characterise the response to multiple receptors. The findings were compared to healthy controls matched for gestational age with normal fetal weight. A total of 24 pregnancies complicated with IUGR and 36 healthy controls were recruited. Platelet reactivity in response to the agonists Arachidonic acid, Adenosine-diphosphate, Epinephrine and Thrombin-receptor activating protein was significantly reduced in the IUGR cohort. There was a nonsignificant trend to decreased reactivity in response to collagen (Table 1 ). In pregnancies complicated by IUGR there is a significant decrease in platelet function compared to healthy pregnant controls. This may reveal valuable insights into the patho-physiology of the disease, and may represent an inadequate growth factor response in IUGR. Further evaluation of the role of platelets may and aid in the development of future interventions for IUGR.